Malaysian white shrimp (P. vannamei) aquaculture: an application of stochastic frontier analysis on technical efficiency - Lim, Ghee Thean; Islam, Gazi Md Nurul; Ismail, Mohd Mansor (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Shrimp aquaculture is playing a vital role in Malaysian agriculture, especially its increasing contribution to economic growth. White shrimp aquaculture is not only the key player in brackish water shrimp aquaculture but also the largest contributor to Malaysian shrimp aquaculture. This study estimates technical efficiency and investigates factors affecting technical inefficiency of Malaysian white shrimp aquaculture. Stochastic frontier analysis with trans-log production model is applied in this study. Malaysian white shrimp aquaculture farmers have achieved an estimated average technical efficiency of 81.2 percent. Land ownership, shrimp seed size and seminar are the factors having significant impacts on technical inefficiency and thereby playing important roles in improving technical efficiency of this industry. This study suggests that seminar should be conducted by shrimp farming extension agents to enhance knowledge of shrimp farmers. Malaysian government should allocate lands and, provide technical and financial supports to develop this industry. Subsidy on shrimp seed should be also given to encourage shrimp farmers to embrace and adopt quality shrimp seed for their farms.